New Insights Into the Social Rumor Characteristics During the COVID-19 Pandemic in China - Lv, Wei; Zhou, Wennan; Gao, Binli; Han, Yefan; Fang, Han (Frontiers in Public Health, 2022)
In the early stage of the COVID-19 outbreak in China, several social rumors in the form of false news, conspiracy theories, and magical cures had ever been shared and spread among the general public at an alarming rate, causing public panic and increasing the complexity and difficulty of social management. Therefore, this study aims to reveal the characteristics and the causing factors of the social rumors during the COVID-19 pandemic. Based on a sample of 1537 rumors collected from Sina Weibo’s debunking account, this paper first divided them into four categories and calculated the risk level of all kinds of rumors. Then combining with the number of COVID-19 confirmed cases, time evolution analysis and correlation analysis were adopted to study the time evolution characteristics, the spatial and temporal correlation characteristics of the rumors, four stages of development were also divided according to the number of rumors. Besides, to extract the key causative factors from fifteen rumors causative factors, the social network analysis method was used to investigate the cause-cause 1-mode network characteristics, the generative cause-rumor 2-mode network characteristics, and the spreading cause-rumor 2-mode characteristics. The results and discussion about the rumor classification and the risk pattern, the time evolution, the spatial and temporal correlation, the rumored cause, and the network structure are helpful for social managers better understanding the mechanism of the rumors and making more timely and effective countermeasures in the face of emergencies. Some common features and experiences can also be referred to by other countries.